2017
DOI: 10.1111/1475-6773.12539
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Statewide Antipsychotic Prescribing after Implementation of Child and Adolescent Psychiatry Consultation Services

Abstract: Statewide antipsychotic prescribing for Medicaid clients fell significantly at different rates following each implementation step of a multilevel consultation and best-practice education service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Consistent with research in Medicaid insured youth, 14‐16 we observed heterogeneity in the impact of PA across age groups. Despite an initial decrease in antipsychotic prevalence among adolescents, there was an upswing in use over the long‐term.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Consistent with research in Medicaid insured youth, 14‐16 we observed heterogeneity in the impact of PA across age groups. Despite an initial decrease in antipsychotic prevalence among adolescents, there was an upswing in use over the long‐term.…”
Section: Discussionsupporting
confidence: 84%
“…Emerging evidence shows that PA has led to reduced antipsychotic prescribing among Medicaid insured youth, with estimates ranging from 30% to 49% decrease in prescribing. Additionally, children have a greater decrease in antipsychotic prescribing than adolescents, suggesting age differences in the impact of PA 14‐17 …”
Section: Introductionmentioning
confidence: 99%
“…58 The PAL also demonstrated high utilization and high PCP program satisfaction, as well as its association with increased use of medication for ADHD and depression/anxiety and decreased use of antipsychotic medication among Medicaid-insured youth. 59,60 Project TEACH demonstrated increased PCP confidence in assessing severity of BH problems, developing BH treatment plans, and prescribing psychotropic medications. 61 While different structures and outcome measures preclude direct comparisons across programs, the findings from the current program, MCPAP, PAL, and TEACH, converge in their demonstration of high utilization and high satisfaction/perceived value among PCP participants.…”
Section: Discussionmentioning
confidence: 99%
“…Significant practice changes can result from a consult-and-review system that does not rely on Medicaid authorization denials (Zito, 2017). For instance, in Washington, the total statewide use of antipsychotics for Medicaid youth decreased by 50%, and in Wyoming there was a 40% decrease in children under 5 using psychotropics, all while receiving generally positive provider feedback about mandatory reviews (Barclay et al, 2017;Hilt et al, 2015).…”
Section: Role Of Psychotropic Medication Oversight Programsmentioning
confidence: 99%